He Tūhononga Whaiaro: A Kaupapa Māori Approach to Mate Wareware (Dementia) and Cognitive Assessment of Older Māori. (April 2022) - Menzies, Oliver; Dudley, Margaret; Garrett, Nick; Elder, Hinemoa; Daniels, Piripi; Wilson, Denise
Aim: The aim of this study is to investigate Māori (Indigenous peoples of Aotearoa New Zealand) understandings of dementia ( mate wareware ) and develop a framework to inform assessment of cognitive impairment. Method: Qualitative, kaupapa Māori (M ā ori approach) research with 241 older Māori ( kaumātua ) involving 17 focus groups across Aotearoa New Zealand (NZ) and eight families ( whānau ) from one region. We thematically analyzed transcribed data from audio-recorded interviews. Results: Two overarching themes, namely, connection ( Tūhononga ) and self ( Whaiaro ), and eight subthemes in particular mind ( hinengaro ), spirit ( wairua ), body ( tinana ), family ( whānau ), social connection ( whanaungatanga ), identity and role ( tuakiri ), place ( wāhi ), and ancestors ( tūpuna ) emerged. Māori language ( Te Reo Māori ) was important for cognitive health. Conclusion: The findings embedded in cultural values improve understanding of dementia ( mate wareware ) in Māori. These themes can inform the assessment of older Māori with cognitive impairment. For those without cognitive impairment, the Tūhononga Whaiaro framework suggests factors potentially crucial for healthy aging in Māori.